Kontribusi Disiplin Kerja Guru Terhadap Kinerja Guru SD - Aji, Deni Kumara; Miyono, Noor; Murniati, Ngurah Ayu Nyoman (Universitas Muria Kudus, 2022)
This study aims to determine the contribution of work discipline to the performance of elementary school teachers in Jambu District. Collecting data using instruments. Data processing using normality test and simple regression test. The results of the teacher's performance normality test show the Asymp value. Sig. (2-tailed) 0.193 and the teacher's work discipline shows the Asymp value. Sig. (2-tailed) 0.094. The value is greater than = 0.05. Thus, it can be concluded that the variable data on teacher work discipline are normally distributed. The results of the regression test show that there is a significant effect of teacher work discipline on performance which is stated in the equation = 86.001 + 0.452 X2 with a correlation strength of 0.355 with a contribution of 0.126 = 12.6%, meaning that the influence of teacher work discipline on teacher performance is 12 .6% and the remaining 87.4% are influenced by other factors.This study aims to determine the contribution of work discipline to the performance of elementary school teachers in Jambu District. Collecting data using instruments. Data processing using normality test and simple regression test. The results of the teacher's performance normality test show the Asymp value. Sig. (2-tailed) 0.193 and the teacher's work discipline shows the Asymp value. Sig. (2-tailed) 0.094. The value is greater than = 0.05. Thus, it can be concluded that the variable data on teacher work discipline are normally distributed. The results of the regression test show that there is a significant effect of teacher work discipline on performance which is stated in the equation = 86.001 + 0.452 X2 with a correlation strength of 0.355 with a contribution of 0.126 = 12.6%, meaning that the influence of teacher work discipline on teacher performance is 12 .6% and the remaining 87.4% are influenced by other factors.